Development of a novel compression-based piezoelectric traffic model for improving the roadways energy harvesting system by applying the celular Atomata traffic model - Gareh S.; Kok B.C.; Yee M.H.; Borhana A.A.; Alswed S.K. (International Journal of Renewable Energy Research, 2023)
Degrees of freedom (mechanics); Energy harvesting; Piezoelectricity; Transducers; Arrival rates; Cellular automaton; Cellular automatons; Cymbal transducer; Mean arrival rate (?); Piezoelectric; Piezoelectric cymbal transducer harvester; Piezoelectric energy harvesters; Two-degree-of-freedom model (2DOF); Two-degree-of-freedom models; Cellular automata